2017
DOI: 10.1016/j.rboe.2017.05.013
|View full text |Cite
|
Sign up to set email alerts
|

What is the best fixation technique for the treatment of supracondylar humerus fractures in children?

Abstract: ObjectiveTo define the best technique for the surgical treatment of supracondylar fracture of the humerus (SFH) in children, evaluating percutaneous pinning with side wires vs. cross-pinning.MethodsRandomized controlled trials using the Medline, CAPES, and BIREME. The criteria for inclusion of articles criteria were: (1) randomized controlled trials (RCTs) comparing percutaneous wire fixation techniques, (2) SFH Gartland II B, III, and IV, and (3) children aged 1–14 years. The following were used as main varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 23 publications
(31 reference statements)
1
17
0
3
Order By: Relevance
“…The most commonly reported post‐operative outcomes were loss of Baumann and carrying angle. Neither were found to have statistically significant differences between both treatment groups, in agreement with previous meta‐analyses results 4–6 . Meta‐analyses have previously investigated functional outcome using Flynn criteria, a grading system incorporating both loss of carrying angle and elbow range of motion as listed in Table 4 23 .…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The most commonly reported post‐operative outcomes were loss of Baumann and carrying angle. Neither were found to have statistically significant differences between both treatment groups, in agreement with previous meta‐analyses results 4–6 . Meta‐analyses have previously investigated functional outcome using Flynn criteria, a grading system incorporating both loss of carrying angle and elbow range of motion as listed in Table 4 23 .…”
Section: Discussionsupporting
confidence: 84%
“…Majority of iatrogenic ulnar nerve injuries are directly associated with medial wire insertion in cross pinning, making treatment‐based analysis of this outcome more appropriate. A higher rate of iatrogenic ulnar nerve injury in cross pinning was also found by other meta‐analyses 3–8,21 . Cause of injury is multifactorial, including blocking of usual anterior nerve translation, direct penetration and stretching around the medial pin 5,22 .…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The incidence of supracondylar humeral fractures in children has increased by 28% in the past decade [ 5 ], while the surgical rate has also increased [ 6 ]. There are several surgical techniques including K-wire, corticoid screw, and elastic intramedullary nail [ 7 , 8 ]; however, the standard surgical treatment for displaced pediatric supracondylar humeral fractures is closed reduction and percutaneous pinning (CRPP), with the placement of a postoperative plaster cast [ 9 , 10 ]. The elbow joint movement can be restricted to varying degrees after the removal of the plaster cast.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of supracondylar fracture of the humerus account for 55 to 75% of patients with elbow fractures [ 3 , 4 ]. For treatment of this fracture, closed reduction and percutaneous pinning, and open reduction and internal fixation were two common managements for supracondylar fracture of the humerus [ 5 ]. Ducic et al [ 6 ] revealed that closed reduction and percutaneous pinning was associated with an increase of the clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%